The Relationship between Financial Development and Renewable Energy Consumption in the European Union-27 Countries - Saimagambetova, Gaukhar; Abubakirova, Aktolkin; Omarova, Aizhan; Kizimbayeva, Azhar (International Journal of Energy Economics and Policy, 2025)
This study examines the effect of financial development on renewable energy consumption for 27 European Union member countries from an asymmetric causality perspective. Panel cointegration and asymmetric causality tests were applied using panel data for the period 2000-2023. The findings show that there is a long-term cointegration relationship between the variables. In addition, the results of the asymmetric Granger causality analysis reveal that financial development has an asymmetric effect on renewable energy consumption. It was determined that positive financial shocks are the Granger cause of positive shocks in renewable energy consumption. However, no significant causality relationship was found between negative financial shocks and negative shocks in renewable energy consumption. These results show that renewable energy consumption increases in periods when financial development increases, but financial contractions do not have a significant effect on this consumption. The findings of the study reveal that integrating financial development with sustainable energy policies can encourage long-term renewable energy investments and support green transformation in European Union countries.